2017
DOI: 10.1111/itor.12480
|View full text |Cite
|
Sign up to set email alerts
|

Variable neighborhood search based approaches to a vehicle scheduling problem in agriculture

Abstract: A vehicle scheduling problem (VSP) that arises from sugar beet transportation within minimum working time under the set of constraints reflecting a real‐life situation is considered. A mixed integer quadratically constrained programming (MIQCP) model of the considered VSP and reformulation to a mixed integer linear program (MILP) are proposed and used within the framework of Lingo 17 solver, producing optimal solutions only for small‐sized problem instances. Two variants of the variable neighborhood search (VN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Variable neighborhood search that is proposed by Mladenović and Hansen [38] does not involve parameters and can find optimal solution of the problem. Variable neighborhood search is applied to solve various combinatorial optimization problem [39][40][41][42]. In current, it is seldom found that variable neighborhood search is used to solve the automatic production system scheduling problem under just-in-time environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Variable neighborhood search that is proposed by Mladenović and Hansen [38] does not involve parameters and can find optimal solution of the problem. Variable neighborhood search is applied to solve various combinatorial optimization problem [39][40][41][42]. In current, it is seldom found that variable neighborhood search is used to solve the automatic production system scheduling problem under just-in-time environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the iterative process and particle flight situations, adaptive inertia weight is employed to dynamically adjusting the inertia weight (Zhan et al., 2009; Nickabadi et al., 2011), thereby balancing the global search and convergence speed. The ND algorithm combines deep search and neighborhood structure strategy and achieves alternative search by using neighborhood structure formed (Hansen et al., 2001; Gao et al., 2008; Kammoun et al., 2017; Anokic et al., 2020).…”
Section: Nd‐pso Algorithmmentioning
confidence: 99%
“…Likewise, Plessen (2019b) optimized the transport resources in agriculture, seeking to develop models that were thought primarily for spraying and fertilizing applications in the fields through a fleet of vehicles. Recently, Anokić et al (2020) developed a transportation planning problem from the sugar beet industry in Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Anokić et al. (2020) developed a transportation planning problem from the sugar beet industry in Serbia.…”
Section: Introductionmentioning
confidence: 99%